Evaluating Evidence Based Practice of Physiotherapists and the Quality of Physiotherapy Services in Selected Health Facilities of Lusaka, Zambia - Joseph Lupenga; Nkweto Natasha Namwila; Esther Munalula Nkandu; Brian Chanda Chiluba; Hastings Kachingwe Shula (The Center for Disability Studies and Services Brawijaya University, 2019)
There is an empirical argument that Physiotherapists have a moral and professional obligation to move away from assessment and treatment methods based on anecdotal testimonies or opinion and upgrade their method of practice to Evidence-Based Practice in order to remain alive in the era of scientific research. It is essential to evaluate the quality of service being delivered by referral hospitals. This study aimed to establish linkages of knowledge and awareness of evidence-based practice in selected hospitals of Lusaka and the service quality at the physiotherapy outpatient departments. This study employed a descriptive cross-sectional study. The study was based on primary data collected through a standardized SERVQUAL tool measuring the mean expectations and perception of performance for the quality of physiotherapy care. A total of 75 respondents including both physiotherapists and patients contributed to the study. Limited utilization of EBP practice was seen with only 3(5.1%) participants always and 26(4.1%) mostly reading research to guide the clinical decision. 18(31%) and 14(24.1%) respectively strongly agreed or agreed that the insufficiency of basic EBP skills was the primary barrier to the application of EBP in clinical practice. A negative mean gap score was observed across all five dimensions of the SERVQUAL tool for patients. Despite Physiotherapists in Lusaka being knowledgeable of evidence-based practice, negative gaps in quality of care being offered still persist, an indication that there is a needs to improve on patients' satisfaction with the services being provided.